PERDAGANGAN INTERNASIONAL DAN PEMBANGUNAN EKONOMI - Santosa, Agus Budi (Fokus Ekonomi, 2006)
Development strategy is the key of the policy or the combination of the policy in its relation to the economy development. The key strategy will also determine the instrument that is used in conducting certain policy. The theory concept of development strategy can be done by using Big Push Theory, Balance Growth and Unbalance Growth. One of the most important strategies in the recent decade is international trade, by which economy growth transmission will trigger the economy development.Keyword: Development Strategy, Big Push Theory, Balance Growth, Unbalance Growth.